Aspek Hukum Pencatatan Perkawinan menurut Hukum Indonesia di Desa Tumpatan Nibung Kecamatan Batang Kuis Kabupaten Deli Serdang - Nisa, Khairun; Hasibuan, H.A. Lawali; Lubis, Zaini Munawir (Universitas Medan Area, 2017)
Legal Aspects of Marriage Registration According to Law of Indonesia in Tumpatan Village Nibung Kecamatan Batang Kuis Deli Serdang DistrictAbstractThe background of this writing is that there are still records of marriages that have not been registered so that the purpose of this writing. A marriage is legal if carried out according to the laws of religion and their respective beliefs. In addition, every marriage must be registered in accordance with the applicable legislation. For those who are Muslim, recording at the Marriage Registrar, Divorce and Referral. Whereas for various non-Muslims, marriage records are conducted at the Civil Registry Office. However, it is still unregistered. The reason is because the cost of a marriage registration is expensive, the procedure is complicated, and people do not know the benefits of a marriage record. The legal consequences are registered, affecting the position of husband and wife, children's status and property position. Marriage carried out by religion and their respective beliefs is legal, even though they are not registered in the office of the civil register, strictly regulated in Article 2 Paragraph (1) of Law Number 1 of 1974 concerning marriage. If the marriage is not recorded, there is no validity of the marriage. This also means that the marriage never existed. In conclusion, according to Article 2 Paragraphs 1 and 2 that marriages are not listed on the Marriage Registrar, then the marriage is considered non-existent.